Storage of pink perch {Nemipterus japonicus) in ice : Chemical, microbiological and sensory assessment - Reddy, G Vidya Sagar; Srikar, L N (Indian Journal of Fisheries, 2011)
The most important objective in postharvesttechftology of fish is to preserve itsfreshness. Many tropical fishes have longershelf life when s:tored in ice than those fromtonperate water;: because of lowÂ» number ofpsychotrophs (Disney et al. 1971). The storagelife of marine fish in ice varies between 9and 21 days (Bramstedt 1965). According toBoyd and Wilson (1978), for every hour fishesare held on deck at temperature between 14*Cand 18*C, they loose the equivalent of one dayshelf life in ice.